“Dosis y efecto de cuatro extractos vegetales para el control de manchas foliares en maní (arachis hypogaea), en el distrito de la banda de shilcayo – San Martín” - Navarro Armas, Marily (2014)
With the aim of determining dose and effect of extracts control fungal diseases of vegetable leaf caused spot by Cercospora arachidicola Hori and rust caused by Puccinea arachidís Sped. in Arachis hypogaea., and evaluate the impact on the cultivation of peanuts. Research work developed in Bello Horizonte - high Polish 7 km from the District of the Banda de Shilcayo, execution and installation was started in September of 2008 to February 2009. Aqueous extracts from Jacaranda copaia, Chenopodioum ambrosioides, Lonchocarpus nicou and Averrhoa were applied ata dose of 2040 ml.L-1 anda witness with water, design was used with 9 treatments and three replications randomized complete block; we evaluate incidence and severity of diseases and in the plant: emergency, number of flowers per blooms, plant height, number of leaflets, weight of filled pods fresh and dry, weight of empty pods and biomass. Rust diseases and cercosporiosis achieved decrease with the implementation of 40 ml/I of Lonchocarpus nicou in both cases in the T8 (10121 mm sheet). The extracts of Lonchocarpus nicou dose of 20 mili, obtained the best results in numbers of flowers (3.0, 25.2 and 25.2 per plant in the three blooms), the numbers of leaflets (78.6 leaflets) and biomass yield (kg 555,6 21 I has). ), and with 40 mi dose.L-1 recorded higher plant (72.4 cm) height and higher performance of filled pods with (622,2 3 kg I has) in fresh and dry (2111, 1 kg I has) Key word: Disease of peanut, extracts vegetable, rust, cercospora